2013
DOI: 10.4102/phcfm.v5i1.426
|View full text |Cite
|
Sign up to set email alerts
|

Community participation of patients 12 months post-stroke in Johannesburg, South Africa

Abstract: BackgroundImprovement in health-related quality of life (HRQL) is the main goal of rehabilitation. The ability of the stroke-patient to participate in various situations signifies successful rehabilitation. The aim of the study was to establish the extent of community participation and the barriers and facilitators to the participation for stroke patients after their discharge.MethodThis study formed part of a larger study focusing on the impact of caregiver education on stroke survivors and their careers. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
55
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(60 citation statements)
references
References 35 publications
3
55
1
1
Order By: Relevance
“…Low levels of participation of stroke survivors in South Africa have also been described by various South African authors 8,10,11 . These authors pointed out challenges with mobility and environmental barriers as reasons for participation restrictions.…”
mentioning
confidence: 61%
See 4 more Smart Citations
“…Low levels of participation of stroke survivors in South Africa have also been described by various South African authors 8,10,11 . These authors pointed out challenges with mobility and environmental barriers as reasons for participation restrictions.…”
mentioning
confidence: 61%
“…Study participants experienced activity limitations as indicated by the mean SIS-3 ADL score of 49.1 and a mean MBI score of 70.58 (Table III 10,11,12 attributed activity limitations to poor physical function and decreased muscle strength, while Rhoda et al 5 did not discuss possible causes. Findings from the current study showed, through statistical analysis, that muscle strength and function did indeed affect the ability to perform activities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations